Thrombotic microangiopathy associated with Valproic acid toxicity - Sean A. Hebert (BMC Nephrology, 2017)
Abstract Background Thrombotic microangiopathy (TMA) is a serious, sometimes life-threatening disorder marked by the presence of endothelial injury and microvascular thrombi. Drug-induced thrombotic microangiopathy (DI-TMA) is one specific TMA syndrome that occurs following drug exposure via drug-dependent antibodies or direct tissue toxicity. Common examples include calcineurin inhibitors Tacrolimus and Cyclosporine and antineoplastics Gemcitabine and Mitomycin. Valproic acid has not been implicated in DI-TMA. We present the first case of a patient meeting clinical criteria for DI-TMA following admission for valproic acid toxicity. Case presentation An adolescent male with difficult to control epilepsy was admitted for impaired hepatic function while on valproic acid therapy. On the third hospital day, he developed severe metabolic lactic acidosis and multiorgan failure, prompting transfer to the pediatric intensive care unit. Progressive anemia and thrombocytopenia instigated an evaluation for thrombotic microangiopathy, where confirmed by concomitant hemolysis, elevated lactate dehydrogenase (LDH), low haptoglobin, and concurrent oliguric acute kidney injury. Thrombotic thrombocytopenic purpura was less likely with adequate ADAMTS13. Discontinuing valproic acid reversed the anemia, thrombocytopenia, and normalized the LDH and haptoglobin, supporting a drug-induced cause for the TMA. Conclusion To the best of our knowledge, this is the first report of drug-induced TMA from valproic acid toxicity.